Investigation of Consumer Preferences in the Fruit Juice Industry: An Application of Conjoint Analysis - Talebi, Hojat (Management Strategies and Engineering Sciences, 2025)
This study aimed to determine the relative importance and part-worth utilities of flavor, pulp content, vitamin and mineral addition, and price in shaping consumer preferences for fruit juice products. A quantitative cross-sectional study was conducted among 384 consumers in Tehran Province, Iran. Data were collected using a structured questionnaire containing 15 fruit juice profiles generated through an orthogonal fractional factorial design from four attributes: flavor at four levels, pulp content at two levels, vitamin and mineral addition at two levels, and price at three levels. Respondents ranked the profiles according to their preferences. The data were analyzed using conjoint analysis and a logistic regression approach in STATA version 17. Part-worth utilities were estimated for each attribute level, and relative importance values were calculated to determine the contribution of each attribute to overall consumer preference. Separate analyses were also performed by gender and age group. Flavor was the most influential attribute, with a relative importance of 57%, followed by price at 21%, pulp content at 19%, and vitamin and mineral addition at 4%. Tropical flavor produced the highest positive part-worth utility, whereas citrus and berry flavors generated negative utilities. Fruit juice without pulp was preferred to juice with pulp. The 17,000-Toman price level had the highest positive utility, while the lowest and highest price levels received negative utilities. Flavor remained the dominant attribute in all gender and age segments. Women preferred tropical flavor and assigned greater importance to price, whereas men preferred melon flavor and placed greater importance on pulp content. Price was most influential among respondents aged 30–40 years, while pulp content was comparatively more important among those aged 40–50 years. Consumer preferences for fruit juice were driven primarily by sensory characteristics, particularly flavor, while nutritional enrichment had only a limited influence; therefore, product development should prioritize preferred flavors, pulp-free formulations, and moderate pricing while accounting for demographic differences.